Řečice – nejvýznamnější lokalita mlžů rodu Pisidium na Vysočině? - Luboš Beran (Malacologica Bohemoslovaca, 2022)
The river pea mussel (Pisidium amnicum) and especially the fine-lined pea mussel (Pisidium tenuilineatum) are among the rare and endangered aquatic molluscs in the Czech Republic. Both species were found in 2021 in the small stream Řečice in the Vysočina region during faunistic surveys of the Nová Říše reservoir and the adjacent part of the Řečice. This finding is the only known occurrence in this region. In the approximately 2 km long section of this stream, numerous populations of P. amnicum were found in six sites, while only a few specimens of P. tenuilineatum were recorded at two sites. The Řečice is one of the most important localities for aquatic molluscs in the Vysočina region and due to the occurrence of the critically endangered P. tenuilineatum, this locality is also important in the entire Czech Republic.